Obesidade abdominal como fator de risco para incidência de insuficiência e deficiência de vitamina D em pessoas maiores de 50 anos - Silva, Thaís Barros Pereira da (Universidade Federal de São Carlos, 2021)
Introduction: Despite being very conflicting, some studies demonstrate a bidirectional relationship between obesity and vitamin D deficiency (≤ 30 nmol/L). However, there is little epidemiological evidence investigating the association between abdominal fat accumulation and the incidence of low serum vitamin D concentrations. Objectives: The aim of the present study was to verify whether abdominal obesity is associated with the incidence of insufficiency and deficiency of vitamin D and whether the presence of osteoporosis and vitamin D supplementation modify such associations. Methods: This is a longitudinal study with four years of follow-up involving participants from the English Longitudinal Study of Ageing (ELSA) aged 50 years and over. The sample consisted of 2,470 participants with vitamin D sufficiency at baseline in ELSA wave 6, defined by serum concentrations of 25-hydroxyvitamin D [25(OH)D] > 50 nmol/L. Abdominal obesity was defined as a waist circumference > 88 cm for women and > 102 cm for men. After four years of follow-up, serum concentrations of 25(OH)D were measured again and incident cases of insufficient (> 30 and ≤ 50 nmol/L) or deficient (≤ 30 nmol/L) 25(OH)D were considered as outcome. Multinomial logistic regression models controlled for sociodemographic, behavioral and clinical characteristics were performed. Results: Abdominal obesity increased the risk of incidence of 25(OH)D insufficiency by 37% (RRR = 1.37; 95% CI 1.02 - 1.84) and of 25(OH)D deficiency by 64 % (RRR = 1.64; 95% CI 1.05 - 2.58). Excluding individuals with osteoporosis or those taking vitamin D supplementation, the risk of insufficiency (RRR = 1.39 95% CI 1.02 – 1.91) and deficiency (RRR = 1.82; 95% CI 1.11 – 2 .97) of 25(OH)D in abdominal obese subjects was even higher. Conclusion: Abdominal obesity appears to be an important factor associated with an increased risk of insufficiency and 25(OH)D deficiency in people aged 50 years and over. These findings demonstrate the importance of a clinical look at obesity and its consequences so that prevention, monitoring and treatment strategies are developed
Abdominal obesity as a risk factor for the incidence of insufficiency and deficiency of vitamin D in older people over 50 years old
Keywords: Envelhecimento; Incidência; Vitamina D; 25(OH)D; Obesidade abdominal; Aging; Incidence; Vitamin D; Abdominal obesity; CIENCIAS DA SAUDE::NUTRICAO::DIETETICA; CIENCIAS DA SAUDE::SAUDE COLETIVA::EPIDEMIOLOGIA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA